The biogeochemical cycling of zinc and zinc isotopes in the North Atlantic Ocean. Issue 10 (21st October 2014) - Conway, Tim M.; John, Seth G.
Abstract Zinc (Zn) is a marine micronutrient, with an overall oceanic distribution mirroring the major macronutrients, especially silicate. Seawater Zn isotope ratios (δ66Zn) are a relatively new oceanographic parameter which may offer insights into the biogeochemical cycling of Zn. To date, the handful of published studies of seawater δ66Zn show the global deep ocean to be both remarkably homogeneous (approximately +0.5‰) and isotopically heavier than the marine sources of Zn (+0.1 to +0.3‰). Here we present the first high‐resolution oceanic section of δ66Zn, from the U.S. GEOTRACES GA03 North Atlantic Transect, from Lisbon to Woods Hole. Throughout the surface ocean, biological uptake and release of isotopically light Zn, together with scavenging of heavier Zn, leads to large variability in δ66Zn. In the ocean below 1000 m, δ66Zn is generally homogeneous (+0.50 ± 0.14‰; 2 SD), though deviations from +0.5‰ allow us to identify specific sources of Zn. The Mediterranean Outflow is characterized by δ66Zn of +0.1 to +0.3‰, while margin sediments are a source of isotopically light Zn (−0.5 to −0.8‰), which we attribute to release of nonregenerated biogenic Zn. Mid‐Atlantic Ridge hydrothermal vents are also a source of light Zn (close to −0.5‰), though Zn is not transported far from the vents. Understanding the biogeochemical cycling of Zn in the modern ocean begins to address the imbalance between the light δ66Zn signature of marine sources and the globally homogeneous deep oceans (δ66Zn of +0.5‰) on long timescales, with overall patterns pointing to sediments as an important sink for isotopically light Zn throughout the oceans.